Literasi Keuangan Syariah Masyarakat Desa Pulai Payung, Kecamatan Ipuh - Henny Satriana; Amrizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the sharia financial literacy of the community in Pulai Payung Village, Ipuh District, Mukomuko Regency. Although Indonesia has great potential for developing sharia finance, the level of sharia financial literacy in rural areas such as Pulai Payung Village is still relatively low. This study used a qualitative method with a case study approach, collecting data through in-depth interviews with the local community. The results show that the community's understanding of the concept of sharia finance is still very limited. Most residents only know that sharia finance does not contain usury, but do not understand other products and principles such as mudharabah, musyarakah, and ijarah. The community's level of knowledge of sharia financial products and institutions is also low, with many preferring conventional financial institutions due to easier accessibility. Skills in managing finances according to sharia principles are also still minimal, with people tending to rely on conventional or informal financial systems. These findings demonstrate the need to improve sharia financial literacy through systematic and sustainable education programs, as well as support from the government and sharia financial institutions. By improving Islamic financial literacy, it is hoped that the public will be able to make better financial decisions, avoid practices that conflict with Islamic teachings, and actively participate in a more inclusive Islamic financial system. This research is expected to serve as a reference for developing Islamic financial literacy in rural areas and strengthening the Islamic financial system in Indonesia.